Cortical interneuron loss and symptom heterogeneity in Huntington disease. Issue 5 (13th May 2014) - Kim, Eric H.; Thu, Doris C. V.; Tippett, Lynette J.; Oorschot, Dorothy E.; Hogg, Virginia M.; Roxburgh, Richard; Synek, Beth J.; Waldvogel, Henry J.; Faull, Richard L. M.
<x xml:space="preserve">Abstract</x> Objective The cellular basis of variable symptoms in Huntington disease (HD) is unclear. One important possibility is that degeneration of the interneurons in the cerebral cortex, which play a critical role in modulating cortical output to the basal ganglia, might play a significant role in the development of variable symptomatology in HD. This study aimed to examine whether symptom variability in HD is specifically associated with variable degeneration of cortical interneurons. Methods We undertook a double‐blind study using stereological cell counting methods to quantify the 3 major types of γ‐aminobutyric acidergic interneurons (calbindin‐D28k, calretinin, parvalbumin) in 13 HD cases of variable motor/mood symptomatology and 15 matched control cases in the primary motor and anterior cingulate cortices. Results In the primary motor cortex, there was a significant loss (57% reduction) of only calbindin interneurons (p = 0.022) in HD cases dominated by motor symptoms, but no significant interneuron loss in cases with a dominant mood phenotype. In contrast, the anterior cingulate cortex showed a major significant loss in all 3 interneuron populations, with 71% loss of calbindin (p = 0.001), 60% loss of calretinin (p = 0.001), and 80% loss of parvalbumin interneurons (p = 0.005) in HD cases with major mood disorder, and no interneuron loss was observed in cases with major motor dysfunction. Interpretation These findings suggest that region‐specific degeneration of cortical interneurons is a key component in understanding the neural basis of symptom heterogeneity in HD. Ann Neurol 2014;75:717–727